p53 mutations in human lymphoid malignancies: association with Burkitt lymphoma and chronic lymphocytic leukemia. - Gianluca Gaïdano; Paola Ballerini; Jerry Z. Gong; Giorgio Inghirami; Antonino Neri; Elizabeth W. Newcomb; Ian Magrath; Dan Knowles; Riccardo Dalla‐Favera (1991)
We have investigated the frequency of p53 mutations in B- and T-cell human lymphoid malignancies, including acute lymphoblastic leukemia, the major subtypes of non-Hodgkin lymphoma, and chronic lymphocytic leukemia. p53 exons 5-9 were studied by using genomic DNA from 197 primary tumors and 27 cell lines by single-strand conformation polymorphism analysis and by direct sequencing of PCR-amplified fragments. Mutations were found associated with (i) Burkitt lymphoma (9/27 biopsies; 17/27 cell lines) and its leukemic counterpart L3-type B-cell acute lymphoblastic leukemia (5/9), both of which also carry activated c-myc oncogenes, and (ii) B-cell chronic lymphocytic leukemia (6/40) and, in particular, its stage of progression known as Richter's transformation (3/7). Mutations were not found at any significant frequency in other types of non-Hodgkin lymphoma or acute lymphoblastic leukemia. In many cases, only the mutated allele was detectable, implying loss of the normal allele. These results suggest that (i) significant differences in the frequency of p53 mutations are present among subtypes of neoplasms derived from the same tissue; (ii) p53 may play a role in tumor progression in B-cell chronic lymphocytic leukemia; (iii) the presence of both p53 loss/inactivation and c-myc oncogene activation may be important in the pathogenesis of Burkitt lymphoma and its leukemic form L3-type B-cell acute lymphoblastic leukemia.